Integrasi Pendidikan Karakter Kepesantrenan dalam Pembelajaran Bahasa Indonesia di Sekolah Dasar - Anggara Dwinata; Aida Arini; Eko Hardinanto; Lutfi Fadilah (Sekolah Tinggi Ilmu Syrari’ah Daru ‘Ulum (STSDU) Lampung Timur., 2026)
This study aims to describe the implementation of Islamic boarding school character values ??in Indonesian language learning in elementary schools. The research method used is a qualitative approach with a literature study research design with a review of journal articles and relevant books. The results of the study show that Indonesian language learning provides comprehensive opportunities for teachers to internalize character values ??such as religiosity, responsibility, honesty, tolerance, and cooperation in a contextual and meaningful manner through real learning activities. Integration of character values ??through components of learning planning and implementation of student-oriented learning activities, role models from teachers, and habituation of positive values ??typical of Islamic boarding schools. The Islamic boarding school character is applied in Indonesian language learning in elementary schools, so that children's learning activities will be directed meaningfully through learning activities such as making Religious Pantun, Islamic Poetry, Islamic Boarding School Literature, Islamic Workshops, Exemplary Islamic Boarding School Figures, mutual respect, conveying ideas politely, appreciating differences, and upholding a sense of tolerance. The conclusion of the study confirms that the integration of Islamic boarding school character values ??in Indonesian language learning has an important role in the formation of spiritual and social character for students in elementary schools.